Effects of multispecies pasture diet and cow breed on milk composition and quality in a seasonal spring-calving dairy production system - Renata Kostovska; Brendan Horan; Gaetan Drouin; John T. Tobin; Tom F. O'Callaghan; Alan L. Kelly; Laura G. Gómez-Mascaraque (Journal of Dairy Science)
ABSTRACT: In recent years, significant emphasis has been placed on the composition of pasture-based cow feed and the potential benefits of incorporating multispecies swards to improve sustainability and biodiversity. This study compared the effects of a conventional perennial ryegrass (PRG) monoculture supported by high-chemical N usage with a low-chemical-N application multispecies sward system (MSS) on the composition and quality of milk across lactation using spring-calving Holstein-Friesian (HF) and Jersey Holstein-Friesian (JFX) cows. Bulk milk samples (n = 144) were collected from each group at morning and evening milking on a weekly basis (n = 36) throughout lactation and analyzed for gross composition and physicochemical properties. Cow breed had a significant effect on milk profile, with milk from HF cows having significantly smaller milk fat globule (MFG) size, higher instability index values, higher yield, and lower total solids levels, compared with JFX cows. Notably, HF cows had increased milk total solids and fat levels when fed on MSS, as opposed to the PRG-fed HF cows. Feeding MSS pasture increased creaming velocity values in mid and late lactation, and resulted in similar milk gross composition to PRG. In comparison to PRG, MSS-fed groups showed significantly increased total solids yield, including higher levels of protein and fat yield. In late lactation, MSS feeding was associated with reduced MFG size. All physicochemical properties studied (MFG size, creaming velocity, instability index) showed decreasing values from early to late lactation stages. Overall, these findings demonstrate the significant effects of cow diet, breed, and stage of lactation on compositional and physicochemical characteristics of milk, with important implications for milk processing and dairy product quality.